Determination and distribution of various antinuclear antibodies in systemic lupus erythematosus patients by using immunoblot testing - Udayasri; Prakasham; Salma (Journal of Medical and Scientific Research, 2018)
Background: Systemic lupus erythematosus (SLE) is defined as a multisystemic inflammation resulting from production autoantibodies against nuclear and cytoplasmic antigen.